PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN PADA RUMAH MAKAN RAJA PISJO DI TENGGARONG - Akbar, Ali (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2016)
The purpose of this study is to investigate and assess the influence of sense (senses), feel (feeling), think (way of thinking), act (habits) and relate (linkage) on customer loyalty in Raja Pisjo restaurant in Tenggarong. This study used quantitative data obtained from questionnaire data. Number samples are 75 people with the retrieval method by means of random sampling. The analysis tool used multiple linear regression analysis with hypothesis testing using the F and t test. The results of test calculations obtained F count F is 44.295 while the value of F table obtained a value of 2.21, it can be said that the variable sense (senses), feel (feeling), think (way of thinking), act (habits) and relate (affinity) jointly able to show its effect on customer loyalty in raja pisjo restaurant in Tenggarong.Based on correlation tables show that variables relate (linkage) has the most dominant influence on customer loyalty in Raja Pisjo Restaurant in Tenggarong namely at 56.3% followed by the variable act (habit) of 50.7%, the variable feel (feeling) 43.7%, variable think (thinking) of 36.6% and a variable sense (senses) by 21.4%, so that the second hypothesis is accepted.Keywords: Experiential Marketing, Customer Loyalty